KAJIAN EKONOMI PROGRAM LONGGAR DI MAKASSAR (Study on Economic Benefit of Longgar Program in Makassar) - Abdul Razak Munir; Maat Pono; Sudarmono Sudarmono (Jurnal Inovasi dan Pelayanan Publik Makassar, 2017)
The purpose of this research are; (1) To identify the community's response to the Lorong Garden (Longgar) program in Makassar; (2) Analyze the economic benefits of the Longgar program in Makassar, especially in improving the welfare of the community; (3) Formulate development strategy of Longgar program in Makassar City. Location of this study will be conducted in Makassar City. The population of this research is all groups of Kelompok Wanita Tani in Makassar City. The activity of this study in the data collection using observation approach and questionnaire. The collected data is then edited, tabulated, and verified first. The data analysis methods used in this study consist of: (1) Descriptive analysis and, (2) T-statistical analysis of paired t tests. The result of the research shows that the perception of society on the garden garden program is positive and high. From the results of questionnaires distributed to the respondents it can be seen that the level of knowledge, objectives, benefits and community support for the Lorong Garden program is high. The community accessed information about Lorong Garden from the socialization activities by the Penyuluh from Badan Ketahanan Pangan and was very supportive for the competition between Lorong Garden with comprehensive criteria. The results also show the economic benefits of the Lorong Garden Program which increases with time. The paired-sample t test results show significant difference in KWT revenues between 2014-2015 and 2016-2017 and that income tends to increase with time.